Novejša spoznanja na področju etiopatogeneze in zdravljenja primarne osteoartroze - Bregar, Martina (Zdravniški vestnik, 2002)
Background. Some new recognitions on the field of osteoarthritis, its ethiopathogenesis and therapy are presented. Conclusions. OA is the most common rheumatic disease of joint which characterize the breakdown of cartilage. It is very painful and disabling disease with an increasing worldwide prevalence. Despite intensive research over past few decades the cause remain unknown and also the treatment remains unsatisfactory, nonspecific, only symptomatic until the expensive joint surgery replacement isnecessary. The need for expensive joint surgery grows because of aging of population all over the world. In research there is important to find the mechanisms in the pathogenesis of the disease and on that base the disease - modified agents, which act against cartilage destruction factors or cause cartilage protection.
Keywords: Dejavniki tveganja; Diagnosis; Etiology; Osteoarthritis; Osteoartritis; osteoartroza; revmatična obolenja; Risk factors; Therapy; zdravljenje